Can I Be Obliged to Believe? - Menssen, Sandra (Religions, 2022)
We build an argument directed to agnostics who think there’s a realistic possibility some specific revelatory claim is true (for instance, the Christian, or Judaic, or Islamic claim) and who find that claim more plausible than its theistic competitors. Though such agnostics may have serious reservations about the claim, perhaps not even deeming the chance it’s true to be at least fifty-fifty, we contend that—surprisingly—it’s obligatory for them to assent to the claim if it provides a means for remediation of wrong-doing. Our focus is the Christian revelatory claim, but the argument’s template can be applied to other religions that, like Christianity, promise to fix the world’s ills in an afterlife.